INDONESIAN FEMALE FACTORY WORKERS: THE GENDERED MIGRATION POLICY IN MALAYSIA - Hamidi, Mashitah (PEOPLE: International Journal of Social Sciences, 2016)
Recruitment of foreign workers by Malaysian employers is subject to the requirements set by the Malaysian government. Immigration policy is one of the platforms through which the government can encourage or discourage and shape migration. The shifts at both the policy/governmental and public levels have impacted not only on the migration pathways of the Indonesian female migrants in this study (that is, who can work and where), but also on the everyday experiences of women migrants in Malaysia, both at work and in public. This paper has provided a discussion of the terms and conditions of employment contracts, recruitment policy, the general public ambivalence about foreign workers in Malaysia, and as well more local Melaka-based perceptions of Indonesian factory workers. I conducted interviews with 13 migration stakeholders. This group consisted of the following: four staff or managers of human resources departments in four factories; three outsourcing agents or staff members; three government officials (two Malaysian and an Indonesian Attaché); three representatives of civil society (an in-house union leader, an Indonesian expatriate involved in a welfare organization for female Indonesian migrants, and a Malaysian trade union organizer). In relation to female migrants, there was a dichotomized view of them either as victims or perpetrators of abuse. While the media reported very little about female factory workers specifically, the discussion demonstrated the intersection between widely circulated ideas on Indonesian women’s sexual laxity and their opportunistic attitude to money. In response to migrant-related issues, the government’s current position on migration is ambiguous and there have been a number of restrictions imposed on recruitment, including an increase in recruitment costs and gender-related policy.